Experiential Learning Enhances Physical Therapist Student Confidence in Management of Neurologically Involved Adults and Children. Issue 3 (September 2018) - Barta, Kristen; Flores, Megan; Edwards, Anna
Abstract : Introduction: Clinical experiences are an integral part of professional physical therapist (PT) education programs. Hands-on engagement helps foster the critical thinking skills necessary to successfully navigate the complexity of clinical practice during a PT student's final clinical internships. As PT students advance through an entry-level professional program, their clinical decision-making skills improve; however, they lack self-confidence in working with both adult and pediatric patients presenting with neurological impairments. The purpose of this study was to explore the effect of experiential learning using community volunteers (both adults and children) with activity and participation restrictions as a result of neurological insult or developmental delay on PT student perceived self-confidence. Methods: A convenience sample of 128 students currently enrolled in a PT education program were recruited. A pretest–posttest survey assessed the students' self-perceived confidence in the evaluation and treatment of a neurologically involved individual across the lifespan. The students completed 4 weeks of experiential learning with one adult and one pediatric community volunteer with a neurological condition in small groups. The four sessions included an initial evaluation, two treatment sessions and one discharge reassessment. An exploratory factor analysis was completed to validate the tool and to determine the factors that make up the survey. Qualitative data (open-ended questions) were analyzed using a grounded theory approach. Results: On average, students reported more self-perceived confidence in the posttest survey than in the pretest survey. This difference was significant t (127) = −13.841, P < .001. Conclusion: Students expressed that more exposure and increased time spent with neurologically involved adults and children could improve their confidence. This study supports the use of experiential learning in PT education programs. Abstract : Supplemental Digital Content is Available in the Text.